An Information Theoretic Learning Artificial Immune Network for Alternative Clustering - Borges, Ederson; Coelho, Guilherme Palermo (Journal of the Brazilian Computer Society, 2024)
Clustering is an unsupervised task employed when there is no prior knowledge about the structure and information contained in the data. Nowadays the amount of information and the dimensionality of data increased. Due to this, several datasets contain samples that can be clustered in different ways, presenting different partitions. Classical algorithms tend to obtain a single partition per execution and also require information like the number of clusters. Immuno-inspired algorithms were developed to reduce some of these drawbacks. They can find alternative solutions without knowing the number of clusters, but high dimensionality reduces their performance leading to low convergence rates. Information Theoretic Learning (ITL) uses statistical information of the data regardless of prior knowledge of the structure of these data and the dimensionality involved. Applied in several papers for clustering, ITL-based algorithms tend to present good performance for this task. This paper presents an immuno-inspired ITL-based algorithm (ITL-aiNet) capable of finding and maintaining high-quality and diverse solutions for datasets regardless of their dimensionality and structure. Real-world image and document datasets of varying dimensions were used in the experiments, allowing different ways of clustering. The results were evaluated using external indices. The proposed approach was capable of maintaining high-quality and diverse solutions, compared to other strategies found in the literature. The indices used to measure the quality and diversity of solutions indicated that the algorithm is capable of finding and maintaining good solutions. Solutions that have greater diversity than other algorithms in some datasets and higher quality in others.